The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1995
DOI: 10.1128/jcm.33.10.2643-2646.1995
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of PCR by aqueous and vitreous fluids

Abstract: The detection of viral nucleic acids in intraocular fluids and tissues by PCR has become increasingly important in clinical ophthalmology. While much attention has been directed toward minimizing false-positive reactions resulting from specimen contamination or amplicon carryover, relatively little attention has been given to the causes of false-negative PCRs. This report describes a PCR inhibitor in normal aqueous and vitreous fluids that can produce false-negative PCR results. As little as 0.5 l of vitreous … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
69
0
2

Year Published

1996
1996
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 165 publications
(73 citation statements)
references
References 14 publications
2
69
0
2
Order By: Relevance
“…Evaluation and comparison of LAMP and PCR for detection of DNA in clinical samples. Previous reports have described clinical samples as containing some PCR inhibitors (8,9,15,21); therefore, DNA preparation is required to obtain sensitive results for PCR assays. In order to clarify whether a DNA preparation procedure was necessary to obtain sensitive results with LAMP, we tested 40 genital and 20 ocular samples, with and without a DNA extraction procedure, by both the LAMP and PCR assays.…”
Section: Specificity Of Lamp Assay a Successful Lamp Reactionmentioning
confidence: 99%
See 1 more Smart Citation
“…Evaluation and comparison of LAMP and PCR for detection of DNA in clinical samples. Previous reports have described clinical samples as containing some PCR inhibitors (8,9,15,21); therefore, DNA preparation is required to obtain sensitive results for PCR assays. In order to clarify whether a DNA preparation procedure was necessary to obtain sensitive results with LAMP, we tested 40 genital and 20 ocular samples, with and without a DNA extraction procedure, by both the LAMP and PCR assays.…”
Section: Specificity Of Lamp Assay a Successful Lamp Reactionmentioning
confidence: 99%
“…Next, we evaluated the necessity of DNA extraction. Biological fluids, e.g., aqueous and vitreous humor, contain substances that inhibit PCR(8,9,15,21).…”
mentioning
confidence: 99%
“…Although no inhibition was observed with fecal samples spiked with SARS-CoV, it does not mean that inhibition problems associated with clinical samples have been eliminated by using silica-or magnetic-based types of RNA extraction. In Drosten et al's (2004) study, inhibition was seen with one PCR assay but not the other using the same extracted RNA; this might because of the types of enzyme and reagents used in the amplification assay (Wiedbrauk et al, 1995). There was no available clinical sample in this investigation, but both Artus and Roche kits have improved detection of SARS-CoV, and the sensitivity in stool samples have reached 78-87% (Drosten et al, 2004) versus 58-63% reported earlier .…”
Section: Discussionmentioning
confidence: 68%
“…DNA collection from swabs is attractive because it is simple, minimally invasive, and even enables self-sampling. However, swab-collected specimens are likely to contain polymerase inhibitors such as secreted minerals, electrolytes, hormones, enzymes, immunoglobulins, and cytokines, as well as topical medications [137,[174][175][176][177]. As a result, many swab tests now on the market remove these inhibitors via extraction methods that are too involved and complex to be suitable for the POC [178].…”
Section: Direct Naats For Oral Dermal and Conjunctival Swabsmentioning
confidence: 99%
“…Rodriguez et al used a similar approach in detecting clinical levels of H1N1 by passing an in-house elution buffer with the sample of interest through a filter paper-based setup, then amplifying on the filter membrane [205]. Future developments could focus on direct reactions with swabs that integrate extraction, Typically, elution either at room temperature [51, 176,[182][183][184][185][186] or with heating [43,44, [187][188][189][190][191] is sufficient to generate PCR-amplifiable template from swabs in solution. These methods of dilution or heating can save over thirty minutes of processing time, as with Nihonyanagi et al's heating protocol to release MRSA in CellEaseII (Biocosm Inc., Hyogo, Japan) diluents [169].…”
Section: Direct Naats For Oral Dermal and Conjunctival Swabsmentioning
confidence: 99%